2022
DOI: 10.1177/09612033221131501
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies among newly diagnosed systemic lupus erythematosus patients and their survival

Abstract: The objective of this study was to evaluate the incidence of malignancies among newly diagnosed systemic lupus erythematosus (SLE) patients compared to reference individuals. Another aim was to assess the survival of SLE patients with malignancy compared to references with malignancy. Finnish adult (>17 years) newly diagnosed SLE patients were identified by their drug reimbursement decisions made during 1.1.2000–31.12.2014 from the register of the Social Insurance Institution. For each case, three populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Although early detection and advanced treatment have greatly improved the survival rate of patients with SLE, malignancy remains a major cause of mortality in these patients, and its incidence is still increasing ( 10 ). Many studies have indicated a certain correlation between patients with SLE and reproductive tract tumors ( 11 ), which results in a lower survival rate ( 12 ). As co-cancer of the reproductive tract is exceedingly uncommon, no reports have indicated an increased risk in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Although early detection and advanced treatment have greatly improved the survival rate of patients with SLE, malignancy remains a major cause of mortality in these patients, and its incidence is still increasing ( 10 ). Many studies have indicated a certain correlation between patients with SLE and reproductive tract tumors ( 11 ), which results in a lower survival rate ( 12 ). As co-cancer of the reproductive tract is exceedingly uncommon, no reports have indicated an increased risk in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Mosca [35] University of Pisa Italy 3 134 67 According to the results of journal analysis, Arthritis Research and Therapy, Frontiers in Endocrinology, Autoimmunity Reviews, and Lupus, were the highest ranked journals in publishing related articles regarding this topic, respectively. [25][26][27][28] Considering that 8 of the top 10 most productive journals in this field of research were situated in Q1, it is evident that research in this area has attained a relatively advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that immune cells aberrant activation, including B cells (3), T cells (4), macrophages (5), eosinophils (6), and dendritic cells (DCs) (7), plays a significant role in SLE. Notably, SLE patients have a higher risk for overall malignancy (8,9), which is one of the leading reasons for death in SLE patients (10). Immune system dysregulation could potentially be clinically significant in the development of cancer (11).…”
Section: Introductionmentioning
confidence: 99%